Transformasi dan Dualisme Kelembagaan dalam Pemerintah Adat Minang: Studi terhadap Nagari Pariangan, Sumatera Barat - Hidayat, Yayan; Febriyanto, Iwan Ismi; Nadzir, Mahalli Hatim (Political Science Program, Universitas Negeri Semarang, 2017)
This paper describes the impact of dualism in institution of Nagari Pariangan caused by contestation of social control between state and local government through the Law no. 5 of 1979 and Regional Policy of Sumatera Barat number 2/2007. As a case of institutional transformation, Nagari Pariangan has faced some notorious shape until it was transformed as nagari. We found that the first transformation was the interest of state, and the second is the interest of local government. The results of the transformation are dualism of institution which has diminished political structure of governance and local values of Nagari society.